Psoriasis in besonderen Lokalisationen = Psoriasis in special localizations - Schmieder, Astrid; Ludwig-Peitsch, Wiebke (Der Hautarzt, 2016)
A large proportion of patients with plaque psoriasis suffer from psoriatic lesions of the scalp, nails, and intertrigines. These locations can also be soley or predominantly affected. Scalp psoriasis, nail psoriasis, and inverse psoriasis are often perceived as particularly stigmatizing. Involvement of these parts of the body is associated with an increased risk of psoriatic arthritis. Location-specific features must be considered when choosing treatment. Evidence for topical therapy of scalp psoriasis with steroids and combinations of steroids and vitamin D analogues is high. These agents are regarded as safe and effective treatments of first choice. Efficacy of TNF antagonists and apremilast is well documented for refractory scalp psoriasis. Nail psoriasis often responds insufficiently to topical therapy. Several effective systemic medications including methotrexate and TNF antagonists are available for treatment of severe forms. Controlled trials for treatment of inverse psoriasis are scarce. Topical steroids, vitamin D analogues, dithranol, and off-label calcineurin inhibitors are used in clinical practice. This review provides a survey on the clinical presentation and current evidence for treatment of psoriasis in challenging locations.